Analisis Loyalitas Kerja Karyawan di UNP Hotel & Convention Center Padang - Biaggi Aldhinata; Waryono Waryono (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research is motivated by problems that occur regarding employee loyalty at UNP Hotel & Convention Center Padang. The purpose of this study is to analyze employee loyalty as reviewed from the indicators: 1) Obedience or compliance, 2) Responsible, 3) Devotion, and 4) Honesty. This research is descriptive with qualitative data obtained through observation, interview, and documentation techniques, with research informants selected using purposive sampling techniques. After that, the data was analyzed through data reduction, data presentation, conclusion drawing and verification. Overall, the results of the study indicate that the analysis of employee work loyalty at UNP Hotel & Convention Center Padang is reviewed from the indicators: 1) Obedience or compliance, it can be concluded that employees are still not loyal, as evidenced by not complying with applicable regulations 2) Responsible, it can be concluded that employees are already loyal, as evidenced by having done their job desk well, 3) Devotion, it can be concluded that employees are already loyal because they have devoted themselves to the company. 4) Honesty, it can be concluded that employees are already loyal, as evidenced by having done their work honestly.